Application of Oxygen-Enriched Aeration in the Production of Bacitracin by Bacillus licheniformis - Flickinger, M. C. (1979)
The physiological effects of controlling the dissolved oxygen tension at 0.01, 0.02, and 0.05 atm by the use of oxygen-enriched aeration were investigated during growth and bacitracin production by Bacillus licheniformis ATCC 10716. Up to a 2.35-fold increase in the final antibiotic yield and a 4-fold increase in the rate of bacitracin synthesis were observed in response to O(2)-enriched aeration. The increase in antibiotic production was accompanied by increased respiratory activity and an increase in the specific productivity of the culture from 1.3 to 3.6 g of antibiotic per g of cell mass produced. Oxygen enrichment of the aeration decreased medium carbohydrate uptake and the maximum specific growth rate of B. licheniformis from 0.6 h(−1) to as low as 0.15 h(−1), depending upon the level of enrichment and the conditions of oxygen transfer rate (impeller speed). The response of this culture to O(2) enrichment suggests that this method of controlling the dissolved oxygen tension for antibiotic-producing cultures may simulate conditions that would occur if the carbon source were fed slowly, as is often employed to optimize antibiotic production. Analysis of the biologically active bacitracins produced by B. licheniformis ATCC 10716 suggested that the ratio of biologically active peptides was not changed by O(2) enrichment, nor were any new biologically active compounds formed.